Longevidade de operárias de Apis mellifera alimentadas com dieta incorporada com entomopatógenos - Colombo, Fernanda Caroline (2016)
Apis mellifera Linnaeus, 1758 bees Linnaeus, 1758 (Hymenoptera: Apidae) are social insects, considered useful because of their importance to ecosystems, because they are responsible for over 80% of the pollination of cultivated plant species in the world and they are honey, propolis, royal jelly, wax and apitoxin producers. But the bees are suffering from the colony collapse disorder and one of the main suspects of this problem is the uncontrolled use of synthetic chemical insecticides. One of the alternatives to reduce the use of these is the use of microbial biological control, however, the effects of bioinsecticides (entomopathogens) on Apis mellifera are still poorly elucidated. The objective of this work was to evaluate the longevity of the workers of A. mellifera fed with a diet incorporated with commercial entomopathogenic B. bassiana and B. thuringiensis, and check possible morphological changes in their midgut, in laboratory conditions. For this, the entomopathogenic fungi and bacteria used were B. bassiana (Product A) in a concentration of 5.0 x 1011 viable conidia.kg-1, B. thuringiensis (Product B, called BtB) in a concentration of 2.5 x 109 viable spores.mg-1 and (C Product, called BtC) in aconcentration of 1.0 x 109 viable spores.mg-1. Two controls were prepared, T1: sterile distilled water and: T2: sterile distilled water + Tween 80® (0.01%). For bioassays, 2 ml of each treatment were incorporated into Candi paste (100g icing sugar and 20 ml honey). For each treatment 80 bees were placed, individually, in flat-bottomed glass tubes (Ø 2.5 cm), covered with cheesecloth containing a piece of cotton soaked in sterile distilled water and Candi folder treatments. The tubes containing the bees were kept in climate chamber (30 ± 2 ° C, U.R. 60% ± 10%, 12 h) and mortality was assessed every six hours for 10 days. Right after the verification of mortality, two bees were separated and randomly selected per treatment for removing the midgut, being these fixed in modified Karnovsky. Midgut samples were processed in standard methodology for Scanning Electron Microscopy (SEM). It was found that the products A, B and C decreased longevity of bees (60,45, 64,12 and 62, 47 hours, respectively) when compared to the witness T1 and T2 (72.97 and 80.77 hours, respectively). In qualitative analysis, carried out in midgut SEM, it was not possible to observe external or internal morphological changes in tissues. It was verified their integrity without breaking signal or damage resulting from the product effect. It wasn’t also verified the presence of B. bassiana and/or B. thuringiensis in the samples. Although the products A, B and C cause reduced longevity, it was not observed the presence of the entomopathogenic fungi and bacteria when the tissues were analyzed by SEM.